Performance Analysis of Partitional and Incremental Clustering - Zuriana Abu Bakar; Mustafa Mat Deris; Arifah Che Alhadi (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2005)
The partitional and incremental clustering are the common models in mining data in large databases.However, some models are better than the others due to the types of data, time complexity, and spacerequirement. This paper describes the performance of partitional and incremental models based on the numberof clusters and threshold values. Experimental studies shows that partitional clustering outperformed when thenumber of cluster increased, while the incremental clustering outperformed when the threshold value decreased.Keywords: Clustering, partitional, incremental, distance.